Viability of Performing Multiple 24-2 Visual Field Examinations at the Same Clinical Visit: The Frontloading Fields Study (FFS) - Phu, Jack; Kalloniatis, Michael (American journal of ophthalmology, 2021)
•Frontloading SITA-Faster tests yield repeatable and reliable results.•Four visual field test results can be obtained in less than 20 minutes.•These results can facilitate adherence to recommendations on frequency of perimetric testing. To assess the viability, in terms of time taken for testing and repeatability, of frontloading (performing multiple perimetric examinations) in a single clinic visit. Reliability enhancement analysis. A total of 329 healthy glaucoma suspect and glaucoma subjects within a glaucoma clinic undergoing perimetric testing using SITA-Faster twice for each eye within the same session were included. Global indices, pointwise sensitivity and probability scores, test duration, and reliability metrics were analysed. For both tests 9.1% of right eye and 6.7% of left eye results were unreliable, with 58.4% and 67.5% of right and left eyes achieving reliable results, respectively; 83.8% of all subjects spent less than 20 minutes performing all tests. Differences in global indices, pointwise sensitivity and probability scores showed no systematic or clinically significant difference between tests one and two for each eye. There was also no systematic difference in the number of test locations identified as defective at the P < .05 level between tests. Test results that were unreliable tended to show more instances of a failed “cluster” criterion that were not repeatable. Frontloading using SITA-Faster was viable for obtaining sets of reliable, repeatable perimetric data in terms of conventional outputs, overcoming practical issues regarding low test reliability using singleton results and confirmation of visual field defects. Despite the need to remain cognisant of the reliability of SITA-Faster, frontloading using this algorithm may be a practical method for meeting recommendations for multiple perimetric data required to make confident inferences about glaucoma state and progression.